Overprint varnish, printed matter, paper substrate or plastic substrate
The overprint varnish, incorporating a photocatalyst with crystalline rutile titanium oxide and divalent copper, along with rosin-modified phenolic resin and rosin ester resin, addresses the limitations of existing varnishes by providing enhanced antibacterial and antiviral properties and preventing yellowing.
Patent Information
- Application Number
- JP2021048410
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-03-23
AI Technical Summary
Existing overprint varnishes lack significant antibacterial and antiviral effects while also being prone to yellowing over time, which compromises their effectiveness and appearance.
An overprint varnish containing a specific amount of a photocatalyst comprising crystalline rutile titanium oxide and a divalent copper compound, combined with a rosin-modified phenolic resin, a wax, and a rosin ester resin, is used to enhance antibacterial and antiviral properties while preventing yellowing.
The proposed overprint varnish achieves a substantial antibacterial and antiviral effect while minimizing the likelihood of yellowing, thereby maintaining the appearance and functionality of printed materials.
Smart Images

Figure 0007658772000001 
Figure 0007658772000002 
Figure 0007658772000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an overprint varnish that is dried to form a varnish film. [Background technology]
[0002] For the purpose of improving the gloss of printed matter and protecting the film of the printed matter, an overprint varnish (also called an overcoat varnish; hereafter sometimes referred to as OP varnish) is used after printing. Specifically, after printing each color of printing ink, a colorless and transparent OP varnish is printed. A known OP varnish is a solvent-based OP varnish that contains an organic solvent and forms a varnish film when dried. (See, for example, Patent Document 1.)
[0003] On the other hand, in recent years, there has been a demand for imparting functionality to the surfaces of various substrates, and there is a need to improve the surface properties of not only printed matter but also plastic materials, molded products, paper substrates, film substrates, packaging materials, etc. In recent years in particular, in addition to physical functionality such as improved gloss and film protection, hygienic functions such as antibacterial and antiviral properties are also desired, and there is an urgent need for antiviral (virus inactivation) measures as a countermeasure against viral infections, particularly those caused by new strains of influenza, SARS (Severe Acute Respiratory Syndrome), and norovirus.
[0004] As an OP varnish composition having antiviral properties, for example, an OP varnish composition characterized by containing polytetrafluoroethylene particles and an antibacterial agent in an OP varnish is known (see, for example, Patent Document 2). However, the zeolite-based inorganic antibacterial agent used in Patent Document 2 has a high antibacterial effect but a low antiviral effect, and there is a problem in that the printed matter tends to yellow over time. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-94443 A [Patent Document 2] Japanese Patent Application Publication No. 11-80643 Summary of the Invention [Problem to be solved by the invention]
[0006] The problem that the present invention aims to solve is to provide an overprint varnish that has strong antibacterial and antiviral effects and prevents printed matter from yellowing over time. [Means for solving the problem]
[0007] The present inventors have solved the problem by providing an overprint varnish containing a specific amount of a photocatalyst that contains titanium oxide, including crystalline rutile-type titanium oxide, and a divalent copper compound.
[0008] That is, the present invention provides an overprint varnish that contains a varnish containing a rosin-modified phenolic resin, a dryer, and a wax, and that contains 0.1 to 5 mass % of the photocatalyst.
[0009] The present invention also provides an overprint varnish according to claim 1 or 2, wherein the varnish contains a rosin-modified phenolic resin and a rosin ester resin, and a mass ratio of rosin-modified phenolic resin:rosin ester resin is 7:3 to 3:7.
[0010] The present invention also provides a printed article having a substrate and a coating of the above-described overprint varnish disposed on the substrate.
[0011] The present invention also provides a paper substrate or a plastic substrate obtained by applying the above-described overprint varnish to a paper substrate or a film.
[0012] The present invention also provides containers and packaging materials using the above-mentioned paper substrate or plastic substrate. Effect of the Invention
[0013] The present invention makes it possible to obtain an overprint varnish that has strong antibacterial and antiviral effects and prevents printed matter from yellowing over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (Overprint varnish) The overprint varnish of the present invention is not particularly limited except that it contains a photocatalyst described later, and may be a composition of a general-purpose overprint varnish in the field of normal printing inks. In general, it contains a varnish, a dryer, and a wax, and a varnish containing a rosin-modified phenolic resin is used as the varnish. In addition, an organic solvent or vegetable oil is used for the purpose of adjusting the viscosity.
[0015] The rosin-modified phenolic resin can be, for example, a resin obtained by reacting a resole having an average number of nuclei of 1.5 to 3.0 obtained by a thermal reaction of formaldehyde and / or paraformaldehyde with a phenol, with a rosin ester resin obtained by reacting a rosin with a polyhydric alcohol, or a resin obtained by reacting a resole having an average number of nuclei of 1.5 to 3.0 with a rosin, followed by esterification with a polyhydric alcohol.
[0016] Examples of phenols used to prepare resols include phenol, cresol, amylphenol, p-tertiary butylphenol, p-octylphenol, p-nonylphenol, p-dodecylphenol, and bisphenol A. Among these, it is preferable to use alkylphenols having a substituent having 4 to 12 carbon atoms at the para position, such as p-tertiary butylphenol, p-octylphenol, p-nonylphenol, and p-dodecylphenol.
[0017] The rosins are not particularly limited and may be any known rosin, including gum rosin, wood rosin, tall oil rosin, polymerized rosin, acid-modified rosin, and rosins purified by distillation or the like.
[0018] When an acid-modified rosin is used, it is preferable to use a dibasic acid or anhydride thereof as a compound used to modify the rosin, such as fumaric acid, maleic acid, maleic anhydride, adipic acid, itaconic acid, phthalic anhydride, isophthalic acid, terephthalic acid, and trimellitic anhydride, and among these, fumaric acid, maleic acid, and maleic anhydride are preferably used.
[0019] Examples of polyhydric alcohols include glycerin, diglycerin, trimethylolethane, trimethylolpropane, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, pentaerythritol, dipentaerythritol, and sorbitol, and among these, glycerin and pentaerythritol are preferably used.
[0020] The weight average molecular weight of the rosin-modified phenolic resin is not particularly limited, but is generally preferably 15,000 or more, more preferably 30,000 or more, and more preferably 150,000 or less. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) under the following conditions.
[0021] Measuring device: Tosoh Corporation HLC-8320GPC Column: Tosoh Corporation TSKgel 4000HXL, TSKgel 3000HXL, TSKgel 2000HXL, TSKgel 1000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation Multistation GPC-8020modelII Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 0.35ml / min Standard: Monodisperse polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.2% by mass of resin solids filtered through a microfilter
[0022] The rosin-modified phenolic resin preferably has a softening point of 150° C. or higher, more preferably 160° C. or higher, and more preferably 200° C. or lower. The softening point in this specification is measured by the ring and ball method in accordance with JIS K5601-2-2, specifically, a brass ring filled with a sample is held horizontally in a glycerin bath, a steel ball of a certain weight is placed in the center of the sample, the bath temperature is raised at a constant rate, the sample gradually softens, the steel ball descends, and the softening point is determined by the reading of a thermometer when the steel ball finally reaches the bottom plate at a thickness of 25 mm.
[0023] Other resins that can be used in combination with the rosin-modified phenolic resin are not particularly limited and may be any known resin. Examples include rosin resin, rosin-modified phenolic resin, rosin ester resin, petroleum resin, acrylic resin, polyester, alkyd resin, petroleum resin-modified rosin-phenolic resin, petroleum resin-modified rosin ester, petroleum resin-modified alkyd resin, alkyd resin-modified rosin-phenolic resin, alkyd resin-modified rosin ester, acrylic-modified rosin ester, urethane-modified rosin-phenolic resin, urethane-modified rosin ester, urethane-modified alkyd resin, epoxy-modified rosin-phenolic resin, epoxy-modified rosin ester, and epoxy-modified alkyd resin. These resins may be used alone or in combination of two or more. The combined use of rosin-modified phenolic resin and rosin ester resin is preferable because it can more effectively impart printability. The combined amount of rosin-modified phenolic resin and rosin ester resin in the overprint varnish is preferably 25% by mass or more, and more preferably 30% by mass or more. The mass ratio of rosin-modified phenolic resin:rosin ester resin is preferably in the range of 7:3 to 3:7, more preferably in the range of 65:35 to 35:65, and even more preferably in the range of 55:45 to 45:55.
[0024] Examples of vegetable oils include non-drying oils such as castor oil, peanut oil, and olive oil; semi-drying oils such as soybean oil, cottonseed oil, rapeseed oil, sesame oil, and corn oil; drying oils such as linseed oil, perilla oil, and tung oil; regenerated vegetable oils; and plant-derived components such as vegetable esters.
[0025] Regenerated vegetable oil can also be used as the vegetable oil. Regenerated vegetable oil is vegetable oil that has been recovered from cooking and regenerated. As the regenerated vegetable oil, oil that has been regenerated with a water content of 0.3% by mass or less, an iodine value of 90 or more, and an acid value of 3 or less is preferable, and more preferably, the iodine value is 100 or more. By reducing the water content to 0.3% by mass or less, it is possible to remove impurities that affect the emulsification behavior of the ink, such as salt contained in the water, and by regenerating with an iodine value of 90 or more, it is possible to make the ink have good drying properties, i.e., oxidative polymerization properties, and by selecting and regenerating vegetable oil with an acid value of 3 or less, it is possible to suppress overemulsification of the ink. Examples of methods for regenerating recovered vegetable oil include filtration, removal of sediment by leaving it to stand, and decolorization with activated clay, etc.
[0026] Examples of fatty acid esters include soybean oil fatty acid methyl esters, soybean oil fatty acid butyl esters, soybean oil fatty acid isobutyl esters, soybean oil fatty acid 2-ethylhexyl esters, linseed oil fatty acid butyl esters, linseed oil fatty acid isobutyl esters, tall oil fatty acid butyl esters, tall oil fatty acid 2-ethylhexyl esters, tall oil octyl esters, tall oil fatty acid pentaerythritol esters, palm oil fatty acid methyl esters, palm oil fatty acid butyl esters, palm oil fatty acid isobutyl esters, palm oil fatty acid 2-ethylhexyl esters, castor oil fatty acid methyl esters, castor oil fatty acid butyl esters, castor oil fatty acid isobutyl esters, and castor oil fatty acid 2-ethylhexyl esters.
[0027] Petroleum-based solvents are usually used as organic solvents. As the petroleum-based solvents, hydrocarbon-based solvents having 6 to 20 carbon atoms are preferably used. Specific examples include paraffin-based solvents such as n-pentane, isopentane, n-hexane, 2-methylpentane, n-heptane, n-octane, and trimethylpentane, naphthene-based solvents such as cyclohexane, cyclohexylmethane, octadecylcyclohexane, and methylisopropylcyclohexane, and "AF Solvent No. 4," "AF Solvent No. 5," "AF Solvent No. 6," and "AF Solvent No. 7" manufactured by ENEOS Corporation.
[0028] Examples of chelating agents include derivatives of aluminum n-butoxide, aluminum iso-butoxide, and aluminum sec-butoxide in which one of the n-butoxy groups, iso-butoxy groups, and sec-butoxy groups is substituted with ethyl acetate or methyl acetoacetate.
[0029] As the dryer, a conventionally known one can be used without any particular limitation. For example, salts of metals such as cobalt, manganese, lead, iron, zinc, calcium, cerium, and rare earth with carboxylic acids such as octylic acid, naphthenic acid, neodecanoic acid, tung oil acid, linseed oil acid, soybean oil acid, and resin acid, i.e., metal soaps, or borates of metals such as cobalt, manganese, lead, iron, zinc, calcium, cerium, and rare earth, etc. These dryers may be used alone or in combination of two or more kinds.
[0030] Examples of wax include natural waxes such as carnauba wax, paraffin wax, and microcrystalline wax, and synthetic waxes such as Fischer-Tropsch wax, polyethylene wax, polypropylene wax, polytetrafluoroethylene wax, polyamide wax, and silicone compounds. These waxes may be used alone or in combination of two or more. It is preferable to use Fischer-Tropsch wax, polyethylene wax, or a composite thereof. The use of these composites can improve the abrasion resistance. The wax is preferably used in an amount of 1% by mass or more in the overprint varnish, and more preferably 3% by mass or more.
[0031] The overprint varnish of the present invention may contain a matting agent in the overprint varnish. By applying such an overprint varnish composition, a matte effect can be imparted to the printed matter. Examples of the matting agent include resin particles such as vinyl chloride resin, urea resin, polyethylene resin, polypropylene resin, polystyrene resin, acrylic resin, and polyamide resin, and one or more of them can be used in combination. Vinyl chloride resin and urea resin are preferred because they can effectively impart a matte effect. The matting agent is preferably 15% by mass or more, and preferably 30% by mass or less, in the overprint varnish.
[0032] Starch can also be preferably used. By using starch in addition to wax, it is possible to improve the anti-offset property. It is preferable to use one having an average particle diameter D50 of 10 μm or more and 20 μm or less. The total content of the particles having an average particle diameter D50 of 2 μm or more and 7 μm or less and the starch having an average particle diameter D50 of 10 μm or more and 20 μm or less in the overprint varnish is preferably 1% by mass or more, and preferably 10% by mass or less.
[0033] Extender pigments can also be preferably used. For example, one or more of known pigments such as clays such as rosewood clay, talc, barium sulfate, calcium carbonate, heavy calcium carbonate, barium carbonate, silica, bentonite, and titanium oxide can be used. By including an extender pigment, the setting of the overprint varnish can be accelerated, and offset can be more effectively suppressed. On the other hand, the gloss of the overprint varnish is reduced by including an extender pigment. Therefore, the content of the extender pigment can be adjusted depending on the effect (gloss / matt) that is desired to be imparted to the printed matter by the overprint varnish and its level. Since the extender pigment has the effect of reducing the gloss of the printed matter, it is desirable to appropriately adjust the amount added depending on the desired design.
[0034] In cases where there is a risk of background scumming during coating, the overprint varnish of the present invention preferably uses one or more stain-preventing agent particles selected from the group consisting of phosphoric acid, ammonium salts of phosphoric acid, alkali metal salts of phosphoric acid, alkaline earth metal dihydrogen salts of phosphoric acid, citric acid, ammonium salts of citric acid, alkali metal salts of citric acid, and magnesium salts of citric acid. The content of the stain-preventing agent particles is preferably 0.01% by mass or more and 0.5% by mass or less, and more preferably 0.01% by mass or more and 0.2% by mass or less, of the overprint varnish. The amount of dampening water used during coating can be reduced, setting delay can be prevented, and anti-setoff properties can be improved.
[0035] The overprint varnish of the present invention may contain other auxiliaries such as antiskinning agents, viscosity modifiers, dispersants, stain inhibitors other than those mentioned above, emulsion modifiers, antioxidants, etc. As these auxiliaries, conventionally known ones can be suitably used.
[0036] (Photocatalyst) The photocatalyst used in the present invention is a photocatalyst containing titanium oxide including crystalline rutile titanium oxide and a divalent copper compound, wherein the crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of the strongest diffraction peak corresponding to rutile titanium oxide of 0.65 degrees or less in an X-ray diffraction pattern obtained by plotting diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation, and the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more and the content of anatase titanium oxide is less than 50 mol %.
[0037] By combining rutile-type titanium oxide, which is highly crystalline, with a divalent copper compound, it is possible to obtain a photocatalyst (a visible light responsive photocatalyst having photocatalytic activity such as antiviral activity in the visible light region) that is excellent in antiviral properties in both bright and dark places and in decomposing organic compounds in bright places. In addition, since divalent copper compounds are less likely to discolor due to oxidation, unlike monovalent copper compounds, discoloration over time can also be suppressed.
[0038] In the present invention, the term "bright place" refers to a place where visible light is present, and the term "dark place" refers to a place where no light is present.
[0039] Here, photocatalytic activity means at least one selected from photoinduced decomposition and photoinduced hydrophilization. Photoinduced decomposition is the action of oxidatively decomposing organic matter adsorbed on the surface treated with titanium oxide, and photoinduced hydrophilization is the action of making the surface treated with titanium oxide hydrophilic and compatible with water. This photoinduced hydrophilization is thought to occur when holes generated by photoexcitation and diffused increase the number of hydroxyl groups on the titanium oxide surface.
[0040] In addition, the term "virus" refers to DNA viruses and RNA viruses, but also includes bacteriophages (hereinafter sometimes abbreviated as "phages"), which are viruses that infect bacteria.
[0041] Next, each component of the photocatalyst will be described. (Titanium dioxide) The titanium oxide used in the photocatalyst contains crystalline rutile type titanium oxide.
[0042] In the present invention, crystalline rutile titanium oxide means titanium oxide in which the full width at half maximum of the strongest diffraction peak corresponding to rutile titanium oxide is 0.65 degrees or less in an X-ray diffraction pattern obtained by plotting the diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation.
[0043] If the full width at half maximum is greater than 0.65 degrees, the crystallinity is poor and antiviral properties in a dark place are not sufficiently expressed. From this viewpoint, the full width at half maximum is preferably 0.6 degrees or less, more preferably 0.5 degrees or less, even more preferably 0.4 degrees or less, and still more preferably 0.35 degrees.
[0044] The content of crystalline rutile titanium oxide in titanium oxide (hereinafter sometimes referred to as "rutile ratio") is 50 mol% or more. When the content is 50 mol% or more, the obtained photocatalyst has sufficient antiviral properties in a bright place and in a dark place, and also has sufficient organic compound decomposition properties in a bright place and, in particular, visible light responsiveness. From this viewpoint, the rutile ratio is preferably 90 mol% or more, and more preferably 94 mol% or more. This rutile ratio is a value measured by XRD, as described later.
[0045] From the above viewpoints, the content of anatase type titanium oxide in titanium oxide (hereinafter sometimes referred to as "anatase ratio") is preferably small, and the anatase ratio is less than 50 mol%, preferably less than 10 mol%, more preferably less than 7 mol%, and even more preferably 0 mol% (i.e., no anatase type titanium oxide is contained). Like the rutile ratio, this anatase ratio is a value measured by XRD.
[0046] The specific surface area of titanium oxide is preferably 1 to 200 m2 / g. When the specific surface area is 1 m2 / g or more, the frequency of contact with viruses, bacteria, and organic compounds increases due to the large specific surface area, and the obtained photocatalyst has excellent antiviral properties in light and dark places, organic compound decomposition properties, and antibacterial properties. On the other hand, when the specific surface area is 200 m2 / g or less, the handling properties are excellent. From these viewpoints, the specific surface area of titanium oxide is more preferably 3 to 100 m2 / g, further preferably 4 to 70 m2 / g, and particularly preferably 8 to 50 m2 / g. Here, the specific surface area is a value measured by the BET method using nitrogen adsorption.
[0047] Titanium oxide can be produced by either a gas phase method or a liquid phase method, and either can be used, but titanium oxide produced by a gas phase method is more preferable.
[0048] The gas phase method is a method of obtaining titanium oxide by gas phase reaction with oxygen using titanium tetrachloride as a raw material. The titanium oxide obtained by the gas phase method has a uniform particle size and is highly crystalline because it is produced through a high-temperature process. As a result, the obtained photocatalyst has good antiviral properties in both bright and dark places, organic compound decomposition properties, and antibacterial properties.
[0049] On the other hand, the liquid phase method is a method of obtaining titanium oxide by hydrolyzing or neutralizing a liquid in which titanium oxide raw materials such as titanium chloride and titanyl sulfate are dissolved. Titanium oxide produced by the liquid phase method tends to have low rutile crystallinity and a large specific surface area. In this case, it is possible to obtain titanium oxide with optimal crystallinity and specific surface area by carrying out calcination or the like, but since this is time-consuming, the gas phase method is more suitable.
[0050] As for titanium oxide, it is advantageous to use commercially available titanium oxide as it is, in view of the catalyst preparation process.
[0051] (divalent copper compound) The photocatalyst contains a divalent copper compound. This divalent copper compound alone does not have antiviral properties in light and dark places, organic compound decomposition properties in light, or visible light responsiveness, but by combining it with the above-mentioned crystalline rutile titanium oxide, the antiviral properties in light and dark places, organic compound decomposition properties in light, and visible light responsiveness are fully expressed. In addition, this divalent copper compound is less susceptible to discoloration due to oxidation, etc., compared to monovalent copper compounds, so that photocatalysts using this divalent copper compound are less susceptible to discoloration.
[0052] The divalent copper compound is not particularly limited, and may be one or two of an inorganic divalent copper compound and an organic divalent copper compound.
[0053] Examples of the divalent copper inorganic compound include one or more selected from the group consisting of copper sulfate, copper nitrate, copper iodate, copper perchlorate, copper oxalate, copper tetraborate, ammonium copper sulfate, copper amidosulfate, and ammonium copper chloride, copper pyrophosphate, inorganic acid salts of divalent copper consisting of copper carbonate, divalent copper halides consisting of copper chloride, copper fluoride, and copper bromide, as well as copper oxide, copper sulfide, azurite, malachite, and copper azide.
[0054] Examples of divalent copper organic compounds include divalent copper carboxylates. Examples of divalent copper carboxylates include copper formate, copper acetate, copper propionate, copper butyrate, copper valerate, copper caproate, copper enanthate, copper caprylate, copper pelargonate, copper caprate, copper myristic acid, copper palmitate, copper margarate, copper stearate, copper oleate, copper lactate, copper malate, copper citrate, copper benzoate, copper phthalate, copper isophthalate, copper terephthalate, copper salicylate, copper mellitic acid, copper oxalate, and copper malonate. Examples of the divalent copper organic compound include one or more selected from the group consisting of copper oxine, copper acetylacetone, copper ethylacetoacetate, copper isovalerate, copper β-resorcylate, copper diacetoacetate, copper formylsuccinate, copper salicylamine, copper bis(2-ethylhexanoate), copper sebacate, and copper naphthenate. Examples of the divalent copper organic compound include one or more selected from the group consisting of copper oxine, copper acetylacetone, copper ethylacetoacetate, copper trifluoromethanesulfonate, copper phthalocyanine, copper ethoxide, copper isopropoxide, copper methoxide, and copper dimethyldithiocarbamate.
[0055] Of the divalent copper compounds, preferred are one or more of copper oxide, divalent copper halides, inorganic acid salts of divalent copper, and carboxylates of divalent copper, for example, one or more of divalent copper halides, inorganic acid salts of divalent copper, and carboxylates of divalent copper.
[0056] Moreover, the divalent copper compound may be a divalent copper compound represented by the following general formula (1). Cu2(OH)3X (1) In general formula (1), X is an anion, preferably a halogen such as Cl, Br, or I, a conjugate base of a carboxylic acid such as CH3COO, a conjugate base of an inorganic acid such as NO3 or (SO4)1 / 2, or OH.
[0057] Among these divalent copper compounds, divalent copper inorganic compounds are more preferable from the viewpoint of economical efficiency and containing less impurities, and copper oxide is even more preferable. Also preferred is a divalent copper compound represented by the above general formula (1). The divalent copper compound may be an anhydride or a hydrate.
[0058] The copper-equivalent content of the divalent copper compound is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of the titanium oxide. When it is 0.01 part by mass or more, the antiviral properties, organic compound decomposition properties, and antibacterial properties in both light and dark places are good. When it is 20 parts by mass or less, the titanium oxide surface is prevented from being covered, and the photocatalytic functions (organic compound decomposition properties, antibacterial properties, etc.) are well exhibited, and the antiviral performance can be improved with a small amount, which is economical. From this viewpoint, the copper-equivalent content of the divalent copper compound is more preferably 0.1 to 20 parts by mass, even more preferably 0.1 to 15 parts by mass, and even more preferably 0.3 to 10 parts by mass relative to 100 parts by mass of the titanium oxide.
[0059] Here, the copper content of the divalent copper compound per 100 parts by mass of titanium oxide can be calculated from the amounts of the raw materials of the divalent copper compound and the raw materials of titanium oxide charged. The copper content can also be determined by measuring the photocatalyst by ICP (inductively coupled plasma) emission spectrometry, which will be described later.
[0060] As described above, the photocatalyst contains titanium oxide including crystalline rutile-type titanium oxide and a divalent copper compound as essential components, but may contain other optional components within the scope that does not impair the object of the present invention. However, from the viewpoint of improving the function as a photocatalyst and antiviral performance, the content of the essential components in the photocatalyst is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and even more preferably 100% by mass.
[0061] The photocatalyst can be produced by carrying out a mixing step of mixing titanium oxide including crystalline rutile-type titanium oxide with a divalent copper compound raw material. The mixture obtained by this mixing step may be further subjected to a heat treatment step to obtain the photocatalyst. The photocatalyst can also be obtained by suspending titanium oxide in an aqueous solution of a copper compound and allowing it to adsorb. Specifically, the photocatalyst can be produced by the method described in Japanese Patent No. 5343176.
[0062] It is preferable that the primary particle size of the photocatalyst is in the range of about 200 to 400 nm and the secondary particle size is about 3 to 10 μm, since the photocatalyst can be dispersed in a coating agent and has excellent photocatalytic activity such as antiviral properties. The primary particle size was measured using a transmission electron microscope (TEM) by directly measuring the size of the primary particles from electron microscope photographs.
[0063] The photocatalyst is contained in the overprint varnish for paper substrates or plastic substrates of the present invention in the range of 0.1% by mass or more and 5% by mass or less in order to exhibit photocatalytic activity such as antiviral properties without impairing various properties inherent to the overprint varnish, such as transparency, printability, and gloss. If the content is less than 0.1% by mass, the desired antiviral and antibacterial properties are not obtained, while if the content is more than 5% by mass, the printed matter will yellow and the gloss of the printed matter will decrease. Among these, the content of 0.5 to 3% by mass is preferable.
[0064] (Method of manufacturing overprint varnish) The overprint varnish of the present invention can be manufactured by a conventional method using the above-mentioned raw materials. In the case of an overprint varnish with a matte effect, for example, the varnish is prepared by heating and dissolving the resins containing the rosin-modified phenolic resin, vegetable oils or fatty acid esters or their mixtures, and further, if necessary, petroleum-based solvents, chelating agents, other auxiliaries, etc., and adding additives, etc., and thoroughly premixing with a stirrer, and then kneading with a shot mill, roll mill, etc. After kneading, the varnish, petroleum-based solvents, vegetable oils, other auxiliaries such as wax, antioxidants, and emulsion regulators are added, and thoroughly mixed and stirred. The photocatalyst and wax may be added during premixing or after kneading.
[0065] The amounts of these ingredients are adjusted according to the viscosity and fluidity required for the overprint varnish. The timing of adding these ingredients is not fixed, but is adjusted appropriately based on the mixed state.
[0066] (Printed material) The printed matter of the present invention is obtained by applying the above-mentioned overprint varnish composition directly onto a substrate, or onto a printed matter printed by a lithographic offset printing machine using an oxidative polymerization type offset printing ink composition. The overprint varnish composition may be applied to the entire surface of the printed matter, or may be applied only to a part of the printed matter. The amount of application may be appropriately adjusted depending on the purpose of applying the overprint varnish composition, and as an example, the coating thickness of the overprint varnish composition after drying is adjusted to about 0.5 μm to 1.5 μm.
[0067] The coating method may be a so-called inline method in which a coating device is incorporated into a lithographic offset printing machine and the overprint varnish is applied following printing with the printing ink composition, or a so-called offline method in which coating is performed using a coater machine equipped with a gravure or flexographic coating device after printing with a lithographic offset printing machine.
[0068] (Paper base material) The substrate is not particularly limited and may be one that is conventionally known, but is particularly suitable for printing on paper substrates such as coated paper, matte coated paper, fine paper, etc. Also usable are backing paper, impregnated paper, cardboard, and paperboard.
[0069] (Plastic substrate) It may also be applied to a plastic substrate. The plastic substrate may be any substrate used for plastic materials, molded products, film substrates, packaging materials, etc. Specific examples include polyamide resins such as nylon 6, nylon 66, and nylon 46; polyester-based resins such as polyethylene terephthalate (hereinafter sometimes referred to as PET), polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; biodegradable resins such as polyhydroxycarboxylic acids such as polylactic acid, aliphatic polyester-based resins such as poly(ethylene succinate) and poly(butylene succinate); polyolefin resins such as polypropylene and polyethylene, polyimide resins, polyarylate resins, and mixtures thereof; and films and laminates thereof made of thermoplastic resins, among which films made of polyethylene terephthalate (PET), polyester, polyamide, polyethylene, and polypropylene can be preferably used. These substrate films may be unstretched or stretched films, and the manufacturing method is not limited. The thickness of the substrate film is not particularly limited, but is usually within the range of 1 to 500 μm. The substrate film is preferably subjected to a corona discharge treatment, and may be vapor-deposited with aluminum, silica, alumina, etc. The substrate may be a laminate (sometimes called a laminate film) having a laminate structure in which the above-mentioned paper substrate or film substrate is laminated by a dry lamination method, a solventless lamination method, or an extrusion lamination method.
[0070] The paper substrate or plastic substrate may further have a printing ink layer. The printing ink used for the printing ink layer is not particularly limited, and it is possible to coat the printing layer with an offset lithographic ink, a gravure printing ink, a flexographic printing ink, an inkjet printing ink, or the like. In particular, as described above, a method of coating a printed matter printed by a lithographic offset printing machine using an oxidative polymerization type offset printing ink composition is industrially preferred.
[0071] (containers, packaging materials) The single-layer paper or film substrate, and laminates having a laminated structure are variously expressed, depending on the industry, the method of use, etc., as functional films, soft packaging films, shrink films, films for packaging daily necessities, films for packaging medicines, films for packaging food, cartons, posters, flyers, CD jackets, direct mail, pamphlets, fine paper, coated paper, art paper, imitation paper, thin paper, cardboard, and various synthetic papers used for packaging cosmetics, beverages, medicines, toys, equipment, etc., but the overprint varnish of the present invention can be used without any particular limitation. Furthermore, these substrates after coating with the overprint varnish of the present invention are formed into containers or packaging materials, and in this case, it is preferable that the overprint varnish of the present invention is coated on the surface that will become the outermost layer when these are used to form containers or packaging materials. EXAMPLES
[0072] The contents and effects of the present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0073] <Preparation of photocatalyst> First, the properties of the titanium oxide raw material (manufactured by Showa Denko Ceramics K.K.) used were measured as follows.
[0074] (BET specific surface area) The BET specific surface area of the titanium oxide raw material was measured using a fully automatic BET specific surface area measuring device "Macsorb, HM model-1208" manufactured by Mountec Co., Ltd. (Rutile content (rutile ratio) and crystallinity (full width at half maximum) in titanium oxide raw material) The content of rutile-type titanium oxide in the titanium oxide raw material (rutilated ratio) and the crystallinity (full width at half maximum) were measured by powder X-ray diffraction.
[0075] That is, X-ray diffraction measurements were performed on the dried titanium oxide raw material using a PANalytical "X'pertPRO" measurement device, a copper target, and Cu-Kα1 radiation under conditions of a tube voltage of 45 kV, a tube current of 40 mA, a measurement range of 2θ = 20 to 100 deg, a sampling width of 0.0167 deg, and a scanning speed of 3.3 deg / min.
[0076] The peak height (Hr) corresponding to rutile crystals, the peak height (Hb) corresponding to brookite crystals, and the peak height (Ha) corresponding to anatase crystals were determined, and the content of rutile titanium oxide in titanium oxide (rutile ratio) was calculated using the following formula.
[0077] Rutile ratio (mol%) = {Hr / (Ha+Hb+Hr)} x 100 Further, the content of anatase type titanium oxide (anatase ratio) and the content of brookite type titanium oxide (brookite ratio) in the titanium oxide were calculated by the following formulas.
[0078] Anatase rate (mol%) = {Ha / (Ha+Hb+Hr)} x 100 Brookite conversion rate (mol%) = {Hb / (Ha+Hb+Hr)} x 100 In the X-ray diffraction pattern obtained by the above X-ray diffraction measurement, the most intense diffraction peak corresponding to rutile-type titanium oxide was selected, and the full width at half maximum was measured.
[0079] (Primary particle size) The average primary particle diameter (DBET) (nm) was calculated by measuring the specific surface area S (m2 / g) of titanium dioxide using the BET single point method and calculating the following formula: DBET = 6000 / (S × ρ) Here, ρ is the density of titanium oxide (g / cm3).
[0080] The measurement results of the titanium oxide raw material used are shown in Table 1.
[0081] [Table 1]
[0082] (Production Example 1) 6 g (100 parts by mass) of titanium oxide raw material (manufactured by Showa Denko Ceramics Co., Ltd.) was suspended in 100 mL of distilled water, and 0.0805 g (0.5 parts by mass in terms of copper) of CuCl2·2H2O (manufactured by Kanto Chemical Co., Ltd.) was added and stirred for 10 minutes. A 1 mol / L aqueous solution of sodium hydroxide (manufactured by Kanto Chemical Co., Ltd.) was added so that the pH became 10, and the mixture was stirred and mixed for 30 minutes to obtain a slurry. This slurry was filtered, and the obtained powder was washed with pure water, dried at 80°C, and crushed in a mixer to obtain a sample (photocatalyst).
[0083] The obtained sample (photocatalyst) was heated in a hydrofluoric acid solution until it was completely dissolved, and the extract was quantified by ICP atomic emission spectrometry. The result was that the amount of copper ions was 0.5 parts by mass per 100 parts by mass of titanium oxide. In other words, the entire amount of copper ions (derived from CuCl2·2H2O) that had been added was supported on the titanium oxide surface.
[0084] The sample (photocatalyst) obtained in Production Example 1 was analyzed by the following method.
[0085] (Rutile titanium dioxide content (rutile ratio) and crystallinity (full width at half maximum)) For the sample (photocatalyst) obtained in Production Example 1, the content of rutile-type titanium oxide in titanium oxide (rutilated ratio) and the crystallinity (full width at half maximum) were measured by powder X-ray diffraction method.
[0086] That is, the dried photocatalyst was ground in a mortar to prepare a powder sample. X-ray diffraction measurements were performed on this sample using a PANalytical X'pertPRO measuring device, a copper target, and Cu-Kα1 radiation under the following conditions: tube voltage 45 kV, tube current 40 mA, measurement range 2θ = 20 to 100 deg, sampling width 0.0167 deg, and scanning speed 3.3 deg / min.
[0087] The peak height (Hr) corresponding to rutile crystals, the peak height (Hb) corresponding to brookite crystals, and the peak height (Ha) corresponding to anatase crystals were determined, and the content of rutile titanium oxide in titanium oxide (rutile ratio) was calculated using the following formula.
[0088] Rutile ratio (mol%) = {Hr / (Ha+Hb+Hr)} x 100 In the X-ray diffraction pattern obtained by the above X-ray diffraction measurement, the most intense diffraction peak corresponding to rutile-type titanium oxide was selected, and the full width at half maximum was measured.
[0089] (Identification of divalent copper compounds) The divalent copper compound present in the sample (photocatalyst) obtained in Production Example 1 was identified by X-ray diffraction measurement using the above-mentioned measuring device and measuring conditions. The results are shown in Table 2.
[0090] [Table 2]
[0091] <Synthesis of rosin modified phenolic resin> Into a four-neck flask equipped with a stirrer, thermometer, reflux condenser and nitrogen gas introduction device, 1000 parts of para-tert-butylphenol, 360 parts of 92% paraformaldehyde, 1000 parts of xylene and 10 parts of 50% sodium hydroxide were charged, the temperature was raised to 95°C and the reaction was carried out for 6 hours while maintaining the same temperature. After that, 300 parts of water and 13 parts of hydrochloric acid were mixed and added to neutralize, and then 1000 parts of water was added. The supernatant was taken out into the same apparatus as above, the temperature was raised to 120°C and stirred for 30 minutes, and the supernatant was taken out to obtain a resol-type phenolic resin with a solid content of 57%.
[0092] In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen gas inlet device, 970 parts of gum rosin with an acid value of 165 mgKOH / g and 14 parts of maleic anhydride were charged, and the temperature was raised to 180°C, 107 parts of pentaerythritol and 2 parts of zinc oxide were added, and the temperature was raised to 250°C and reacted while maintaining the same temperature until the acid value became 20 mgKOH / g or less. After that, the temperature was lowered to 180°C, and while maintaining the same temperature, a resol-type phenolic resin was dropped using a dropping funnel at a dropping rate of 2.5 parts / min, and the dropping was stopped when the 25°C Gardner viscosity of a 50% toluene solution became F-G, and the resin was taken out after 30 minutes to obtain a rosin-modified phenolic resin.
[0093] <Production of rosin modified phenolic resin varnish> In a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet device, 440 parts of rosin-modified phenolic resin and 140 parts of soybean salad oil were charged and heated and stirred at 180°C for 1 hour. Then, 410 parts of AF Solvent No. 6 was added, the temperature was lowered to 160°C, 10 parts of ethyl acetoacetate aluminum di-n-butylate was added, and the same temperature was maintained for 1 hour to obtain a rosin-modified phenolic resin varnish (resin amount 44% by mass).
[0094] <Synthesis of rosin ester resin> 1000 parts of gum rosin (acid value 165 KOHmg / g) and 106 parts of fumaric acid were put into a four-neck flask equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet device, and heated and stirred at 220°C for 1 hour under a nitrogen stream to obtain a reaction mixture containing acid-modified gum rosin and unreacted gum rosin with an acid value of 242 KOHmg / g, after which 317 parts of linseed oil and 162 parts of pentaerythritol were added and mixed, and 1.5 parts of magnesium oxide were further added as a catalyst and stirred and mixed, resulting in a temperature inside the reaction vessel of 161°C. Next, the reaction vessel was heated and reacted while increasing the temperature to 270°C at a rate of 30°C / hr, and then further reacted at 270°C until the acid value became 20 KOHmg / g or less, to obtain a rosin ester resin containing modified rosin ester resin, unreacted linseed oil, and pentaerythritol.
[0095] <Production of rosin ester resin varnish> 520 parts of rosin ester resin, 170 parts of linseed oil, and 300 parts of AF Solvent No. 6 were added to a four-neck flask equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet device, and the mixture was kept at 200°C for 30 minutes with stirring to adjust the viscosity to within the range of 1,000 to 2,000 dPa·s. The mixture was then cooled to 160°C, and 10 parts of ethyl acetoacetate aluminum di-n-butylate was added, after which the mixture was heated to 200°C and kept at that temperature for 60 minutes to obtain a rosin ester resin varnish (resin amount 52% by mass).
[0096] <Polyethylene wax compound> 35 parts of polyethylene wax and 65 parts of soybean salad oil are heated and stirred, then cooled to room temperature. The resulting compound was used.
[0097] <Manganese octylate solution> A solution of 50 parts of manganese octylate dissolved in 50 parts of soybean salad oil was used.
[0098] <Organic solvent> AF6 solvent was used.
[0099] <Method of manufacturing overprint varnish> Various overprint varnishes were obtained by mixing the overprint varnishes of Examples 1 to 8 and Comparative Examples 1 to 5 using a stirrer according to the compositions in Tables 3 and 4. Note that blanks in the tables indicate that no varnish was added.
[0100] (Evaluation items) (1) Table evaluation The overprint varnish was printed under the following conditions, and the printed matter after drying was evaluated for antibacterial properties, antiviral properties, yellowing, gloss, and abrasion resistance.
[0101] <Condition> Printing machine: RI tester Printing paper: OK Topcoat Plus Amount: 0.125cc
[0102] (Antibacterial) A drop of bacterial liquid was applied to the printed surface of the overprint varnish, and the number of live bacteria was measured after 24 hours at 35°C and 90% humidity. If the number of bacteria inoculated was less than 1 / 1000, it was marked as ◎, if it was less than 1 / 100, it was marked as 〇, and otherwise it was marked as ×. Two types of bacteria were evaluated: Staphylococcus aureus and Escherichia coli.
[0103] (Antiviral) A virus liquid is dropped onto the printed surface of the overprint varnish, and the number of viruses is measured after 24 hours at 25°C. If the number of viruses is less than 1 / 1000 of the inoculated number, it is marked as ◎, if it is less than 1 / 100, it is marked as 〇, and otherwise it is marked as ×. Two types of viruses were evaluated: influenza A virus and feline calicivirus.
[0104] (Yellowing of printed matter) After the overprint varnish was passed through an ultraviolet irradiation device, the yellowing of the printed surface was visually evaluated. If the yellowing was about the same as that of the overprint varnish without the antibacterial or antiviral agent added, it was marked with an ⊚, if slight yellowing was observed, it was marked with an ◯, and if yellowing was observed, it was marked with an ×.
[0105] (Glossy) The gloss of the printed surface of the overprint varnish was visually evaluated. If the gloss was about the same as that of the overprint varnish without the addition of the antibacterial or antiviral agent, it was marked with an ⊚, if the gloss was slightly lower, it was marked with an ◯, and if the gloss was low, it was marked with an ×.
[0106] (Abrasion resistance test) Using a Gakushin-type friction tester, the printed matter with the overprint varnish was rubbed 10 times with a load of 500g. If the wear was about the same as that of the overprint varnish without added antibacterial or antiviral agents, it was marked with an ◎, if there was slightly more wear, it was marked with an ◯, and if there was a lot of wear, it was marked with an ×.
[0107] (Printability test) <Printing conditions> Printing machine: LITHRONE G40 (manufactured by Komori Corporation) Paper: OK Topcoat+ (Oji Paper Co., Ltd.) Dampening solution: Presarto-SD100 2.5% diluted with tap water (DIC Graphics, Inc.) ·Printing speed: 10,000 sheets / hour - Version: SONORA (Kodak LLC)
[0108] The printability was checked by printing 5,000 copies of each overprint varnish on the above-mentioned printing machine. If the printability was about the same as that of overprint varnish without added antibacterial or antiviral agents, it was marked with an ⊚, if the printability was slightly worse, it was marked with an ◯, and if the printability was poor, it was marked with an ×.
[0109] The results are shown in Tables 3 and 4. Note that blank spaces indicate no blend.
[0110] [Table 3]
[0111] [Table 4]
[0112] From the above results, it is clear that the overprint varnish of the present embodiment has a strong antibacterial and antiviral effect and prevents printed matter from yellowing over time.
Claims
1. An overprint varnish containing a varnish containing a rosin-modified phenolic resin, a dryer, and a wax, the overprint varnish containing a photocatalyst, The photocatalyst contains titanium oxide including crystalline rutile-type titanium oxide and a divalent copper compound, the crystalline rutile titanium oxide is a titanium oxide having a full width at half maximum of the strongest diffraction peak corresponding to rutile titanium oxide of 0.65 degrees or less in an X-ray diffraction pattern obtained by plotting diffraction line intensity against the diffraction angle 2θ using Cu-Kα radiation, and the content of the crystalline rutile titanium oxide in the titanium oxide is 50 mol % or more and the content of anatase titanium oxide is less than 50 mol %, The overprint varnish is characterized in that the overprint varnish contains 0.1 to 5 mass % of the photocatalyst.
2. An overprint varnish as described in claim 1, wherein the overprint varnish contains 0.1 to 3 mass % of the photocatalyst.
3. 3. The overprint varnish according to claim 1, wherein the varnish comprises a rosin-modified phenolic resin and a rosin ester resin, and the mass ratio of the rosin-modified phenolic resin:rosin ester resin is 7:3 to 3:
7.
4. A printed matter comprising a substrate and a printed coating of the overprint varnish according to any one of claims 1 to 3 disposed on the substrate.
5. A paper substrate or a plastic substrate comprising the overprint varnish according to any one of claims 1 to 3 applied to the paper substrate or film.
6. The paper or plastic substrate according to claim 5 , further comprising a printing ink layer.
7. A container or packaging material using the paper substrate or plastic substrate according to claim 5 or 6.
Citation Information
Patent Citations
Overprinting varnish composition
JP1999080643A
Antibacterial / antifungal resin composition and printed matter using the same
JP2006206803A
Planographic printing ink
JP2010260896A
Overprint varnish composition and printed matter
JP2019094443A
Copper-and-titanium-containing composition and production method therefor
WO2013094573A1